Моделирование автономной энергосистемы постоянного тока с асинхронными генераторами - Мазуренко, Леонид Иванович; Джура, Александр Васильевич; Романенко, Владимир Иванович (НТУ "ХПИ", 2014)
Проведены численные исследования электромеханических процессов в автономной энергосистеме постоянного тока с бесконтактными асинхронными генераторами. Расчеты выполнены на основе ранее предложенной авторами модели, которая включает взаимосвязанные математические модели дизелей, генераторов, их систем возбуждения, систем управления возбуждением генераторов и контроллера распределения мощности в системе. Также предложен и учтен при моделировании алгоритм работы электронного регулятора частоты вращения дизелей. Результатами численных экспериментов подтверждена эффективность предложенных подходов к регулированию электромеханических процессов в системе.

Inverter excited induction generators (IEIG) because of their ruggedness and brushless construction are well suited for autonomous applications. Equipped with electronic excitation systems the IEIGs can generate stabilized dc voltage and may be integrated in dc autonomous power systems (APS). The dc APS with diesel (gas) generators are potentially more effective than ac APS due to the possibility of varying diesel engine speed. In this paper a dc APS equipped with two IEIGs operated parallel on a common load and driven by diesel engines is simulated. The dc APS model used includes models of diesel engines, induction machines and inverters with taking into account saturation effect, IEIG and diesel engine control systems. Active energy control in the system is provided in accordance with the reference power curves. The results of simulation have shown stable operation of the system with the developed control techniques.
Simulation of a dc autonomous energy system with induction generators
Keywords: асинхронный генератор; дизели; автономная энергосистема; induction generator; diesel; autonomous energy system